Corticosteroids in sepsis: an updated systematic review and meta-analysis (protocol). Issue 6 (30th June 2017) - Rochwerg, Bram; Oczkowski, Simon; Siemieniuk, Reed Alexander; Menon, Kusum; Szczeklik, Wojciech; English, Shane; Agoritsas, Thomas; Belley-Cote, Emilie; D'Aragon, Frédérick; Alhazzani, Waleed; Duan, Erick; Gossack-Keenan, Kira; et al.
Abstract : Introduction: Sepsis is associated with a dysregulated host response to infection and impaired endogenous corticosteroid metabolism. As such, therapeutic use of exogenous corticosteroids is a promising adjunctive intervention. Despite a large number of trials examining this research question, uncertainty persists regarding the effect of corticosteroids on survival in sepsis. Several large randomised controlled trials have been published recently prompting a re-evaluation of the available literature. Methods and analysis: A rigorous and reproducible search and screening process from a Cochrane review on the same topic was comprehensive to October 2014. We will search MEDLINE, EMBASE, LILACS, the Cochrane trial registry and clinicaltrials.gov for eligible randomised controlled trials investigating the use of corticosteroids in patients with sepsis from September 2014. Outcomes have been chosen by a semi-independent guideline panel, created in the context of a parallel BMJ Rapid Recommendation on the topic. This panel includes clinicians, content experts, methodologists and patient representatives, who will help identify patient-important outcomes that are critical for deciding whether to use or not use corticosteroids in sepsis. Two reviewers will independently screen and identify eligible studies; a third reviewer will resolve any disagreements. We will use RevMan to pool effect estimates from included studies for each outcome using a random-effect model. We will present the results as relative risk with 95% CI for dichotomous outcomes and as mean difference or standardised mean difference for continuous outcomes with 95% CI. We will assess the certainty of evidence at the outcome level using the Grading of Recommendations, Assessment, Development and Evaluation approach. We will conduct a priori subgroup analyses, which have been chosen by the parallel BMJ Rapid Recommendation panel. Ethics and dissemination: The aim of this systematic review is to summarise the updated evidence on the efficacy and safety of corticosteroids in patients with sepsis. Trial registration number: CRD42017058537.